Estrategias metodológicas en el refuerzo académico en el área de matemática de los estudiantes del octavo año de educación general básica, de la unidad educativa Manuel Gonzalo Albán Rumazo de la parroquia Aláquez, cantón Latacunga durante el periodo 2014-2015 - Chiluisa Rivera, Silvia Yesenia (2015)
The general aim of this investigation was to elaborate training shops about methodological strategies in the academic reinforcement in the mathematics area of the eighth year students, of the Manuel Gonzalo Albán Rumazo Educative Unit from the Aláquez parish, Latacunga canton during the period 2014-2015. The problem was investigated how the methodological strategies affect the academic support? The methodology used was descriptive level and type of field and the bibliographic that allowed detailing the characteristics of the study problem. The conclusions reached were: teachers do not use appropriate strategies in teaching methodology, students not proficient learning methods and sometimes parents worry about their children's homework….